Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 4134 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Rhincodon typus Smith, 1828", "HasCoordinate is true" ] } The dataset includes 4134 records from 27 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0002360-150721130643939/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences